Inhibition of prostaglandin synthetase in human rectal mucosa. Issue 3 (March 1983) - Hawkey, C J; Lo Casto, M
Abstract : Miniaturised methods have been used to construct dose-response curves for the effects of inhibitory drugs on prostaglandin synthesis using individual rectal biopsies obtained from patients with ulcerative colitis. The potency of different drugs has been compared. Sulphasalazine, 5 amino salicylic acid (5-ASA) and N-acetyl 5-ASA inhibited prostaglandin synthesis at high concentration, but sulphapyridine and prednisolone did not. Indomethacin and flurbiprofen were considerably more potent inhibitors. These data imply that sulphasalazine does not act by simple inhibition of prostaglandin synthesis but leave open the possibility that sulphasalazine or 5-ASA may be inhibitors of the synthesis of related lipoxygenase products.